The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d2nj04470f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photoelectrochemical water oxidation over a surface-hydroxylated BiVO4photoanode: advantageous charge separation and water dissociation

Abstract: Bismuth vanadate (BiVO4) is one of the most effective photoanode materials for photoelectrochemical water splitting, while its reaction rate is greatly limited by the poor separation efficiency of photo-generated charges...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The dissociation of surface water (leading to surface hydroxyl) on BiVO 4 increases the complexity of reactions and has a profound impact on the formation of surface polaron and carrier dynamics. For instance, Li et al discovered that surface hydroxylation of the BiVO 4 photoanode improves photogenerated charges separation, resulting in an increase in photocurrent density by 4.75 times . By using ambient pressure resonant photoemission spectroscopy combined with first-principles calculations, Wang et al reported that dissociated water molecules caused hydroxylation of VO 4 tetrahedron on BiVO 4 (010), leading to an enhanced stability of the surface polarons and an alternation of the surface electronic structure .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The dissociation of surface water (leading to surface hydroxyl) on BiVO 4 increases the complexity of reactions and has a profound impact on the formation of surface polaron and carrier dynamics. For instance, Li et al discovered that surface hydroxylation of the BiVO 4 photoanode improves photogenerated charges separation, resulting in an increase in photocurrent density by 4.75 times . By using ambient pressure resonant photoemission spectroscopy combined with first-principles calculations, Wang et al reported that dissociated water molecules caused hydroxylation of VO 4 tetrahedron on BiVO 4 (010), leading to an enhanced stability of the surface polarons and an alternation of the surface electronic structure .…”
mentioning
confidence: 99%
“…For instance, Li et al discovered that surface hydroxylation of the BiVO 4 photoanode improves photogenerated charges separation, resulting in an increase in photocurrent density by 4.75 times. 27 By using ambient pressure resonant photoemission spectroscopy combined with first-principles calculations, Wang et al reported that dissociated water molecules caused hydroxylation of VO 4 tetrahedron on BiVO 4 (010), leading to an enhanced stability of the surface polarons and an alternation of the surface electronic structure. 28 Surface hydroxylation of metal oxides is commonly observed in the photocatalytic water decomposition process; however, the effect of surface hydroxylation on polaron dynamics is still a mystery and requires a detailed time-domain study of the polaron coupled charge carrier dynamics.…”
mentioning
confidence: 99%